International financial reporting standards desk reference : overview, guide, and dictionary - Hussey, Roger (Wiley, 2005)
"This book is written by authors who clearly understand the challenges facing all who seek to understand and apply international standards. I recommend it to you." From the Foreword by Sir David Tweedie Chair of the International Accounting Standards BoardIn this defining resource, authors Roger Hussey and Audra Ong have compiled everything accountants, executives, and organizations in different countries need to reach agreement on accounting rules and standards.